Non-adherence to immunosuppressants following renal transplantation: a protocol for a systematic review. Issue 9 (28th September 2017) - Hucker, Abigail; Bunn, Frances; Carpenter, Lewis; Lawrence, Christopher; Farrington, Ken; Sharma, Shivani
Abstract : Introduction: Adherence to immunosuppressant medication is essential for renal transplant recipients. This review aims to summarise what is known about non-adherence, with a view to providing comprehensive evidence to inform strategies aimed at advancing adherent behaviour. Methods and analysis: A systematic review of quantitative studies that report adherence to immunosuppressants in adult (over 18 years) renal transplant recipients. The review will follow the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines; study quality will be assessed using the Downs and Black checklist. Systematic searches will be completed across relevant databases. Two reviewers will independently extract data using a predefined data extraction form. We will summarise the operationalisation of adherence across studies and use narrative synthesis to identify factors associated with non-adherence. A meta-analysis will be conducted if there is sufficient homogeneity, and available data, across studies to estimate the prevalence of non-adherence in renal transplant recipients. Heterogeneity will be assessed using the I 2 test. Survival analysis will be conducted to estimate hazard ratios to explore the impact of non-adherence on graft survival, graft failure and patient survival. Ethics and dissemination: Findings will be published in a peer-reviewed journal and disseminated at conferences for professionals and researchers. Review outcomes will help support clinical practice by highlighting the extent of non-adherence among adults, and in doing so, signpost the need for suitable intervention. Trial registration number: PROSPERO registration number (CRD42016038751).